2017
DOI: 10.1177/2158244017704685
|View full text |Cite
|
Sign up to set email alerts
|

Mindful Construal Diaries: A Less Anxious, More Mindful, and More Self-Compassionate Method of Eating

Abstract: Mindful construal diaries were found to assist in weight regulation during a long-term intervention. The current study attempted to expand previous findings by testing the consideration (or priming) of questions within the diary (instead of filling in the answers), and investigated levels of state mindfulness, state self-compassion, and state anxiety in an observational trial of pre-to postintervention. Forty-five participants completed State Mindfulness, State Self-Compassion, and State Anxiety scales before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

6
4

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 40 publications
2
36
0
Order By: Relevance
“…Overall, the current study supported the notion that eating in response to stress can be influenced by mindfulness (Hussein, Egan, & Mantzios, 2017;Jordan, Wang, Donatoni, & Meier, 2014;Marchiori & Papies, 2014). The findings suggest that universities should provide awareness on healthy eating by promoting mindfulness and mindful eating (Blotnicky, Mann, & Joy, 2015;El Ansari et al, 2015;Mantzios & Giannou, 2014;Pool, Delplanque, Coppin, & Sander, 2015).…”
Section: Discussionsupporting
confidence: 78%
“…Overall, the current study supported the notion that eating in response to stress can be influenced by mindfulness (Hussein, Egan, & Mantzios, 2017;Jordan, Wang, Donatoni, & Meier, 2014;Marchiori & Papies, 2014). The findings suggest that universities should provide awareness on healthy eating by promoting mindfulness and mindful eating (Blotnicky, Mann, & Joy, 2015;El Ansari et al, 2015;Mantzios & Giannou, 2014;Pool, Delplanque, Coppin, & Sander, 2015).…”
Section: Discussionsupporting
confidence: 78%
“…In their research, this was not true for an experimental group that received a short selfcompassionate induction to cope after the experience of breaking the diet. Following this work, further research has shown that self-compassion plays a significant role in maintaining weight (see Mantzios, Wilson, Linnell, & Morris, [21]), in weight loss [22], [23], and with different practices (i.e., mindful diaries instead of meditation -see Mantzios & Wilson, [24] and Hussein, Egan, & Mantzios, [25]. Participants benefited from self-compassion by breaking the negative cycle of shame, body image dissatisfaction and the drive for thinness when investigating women with and without eating disorders [26].…”
Section: Introductionmentioning
confidence: 84%
“…Dalen et al (2010) and Lillis et al (2009) used mindfulness and mindful eating principles to aid overweight individuals and found a significant reduction in weight and psychological distress. Mantzios and Wilson (2014b) developed a mindful diary that followed the principles of mindful eating and showed success in the loss and maintenance of weight, while Hussein, Egan, and Mantzios (2017) showed that diaries enhanced levels of mindfulness and self-compassion and lowered anxiety by simply considering the questions of the diary rather than writing the answers. Overall research has shown that the mindfulness eating diaries were effective in reducing weight and in assisting with psychological wellbeing, in line with most research within the literature.…”
Section: Introductionmentioning
confidence: 99%